Penerapan model pembelajaran kooperatif tipe group investigation untuk meningkatkan pemahaman konsep kegiatan ekonomi pada peserta didik kelas IV sekolah dasar - Elisa Nursanti (Didaktika Dwija Indria, 2019)
The purpose of the research is to improve of concept comprehension on economy activity by applying cooperative learning model type Group Investigation. The subjects were IV grade students of SDN 02 Gedongan in academic year 2018/ 2019, totaling 20 students. This research was a classroom action research which was held in two cycles. There were four stages in each cycle, which was planning, action, observation, and reflection. The data collection techniques were interviews, observations, tests, and documentation. Data analysis techniques, interactive analysis models and comparative descriptive statistics. Data validity using source triangulation and technical triangulation. Results research to show that average class on preaction class score is 51,55 with 0 % classical completeness. Then class average value increased in cycle I to 71,42 with 42,11 % classical completeness, and in cycle II increased again to 79,55 with 84,21 % classical completeness. Based on results research, can concluded that application of cooperative learning model type Group Investigation can improve of concept comprehension on economy activity on the IV grade students of SD Negeri 02 Gedongan in academic year 2018/ 2019.        Keywords: concept comprehension, group investigation model, economy activity, elementary School